Islamic Entrepreneurship Model Based on Local Wisdom and Competitiveness - Buhaerah; Ahdar; Musyarif (Al-Ishlah: Jurnal Pendidikan Islam, 2020)
Implementation of research-based dedication program with the title of development of Islamic Entrepreneurship Model (IEM) based on local competitiveness aims; (1) Making IEM is a reference for the government or policy determinant to create and direct the business people uphold Islamic values; (2) to make the community have an Islamic entrepreneurial soul, local wisdom-based, and competitive; (3) Increased business management skills and good financial management; and (4) implementing IEM in the form of training and mentoring for the community. The IEM development process includes three phases; (1) The development of IEM, (2) implementation and the assessment, and (3) Monitoring and evaluation. Some factors that are individual according to Islam that entrepreneurs need to have are fathonah, amanah, shiddiq, tabligh, and istiqomah. In addition to things that are inherently in entrepreneur, there are also external factors that can support the success of entrepreneurs including the existence of a conducive legal basis in the form of legislation that supports the growing and development of entrepreneurship. The existence of culture and mindset that supports entrepreneurship as a source of living. The IEM program held in South Sulawesi in 2019 has taken up by 76%. The IEM Program that is implemented for the people of business has reached the goal 80% namely: Increased business management skills and financial management for business people. Creating an entrepreneurial training method that is appropriate for the community of businessmen who are pioneering entrepreneurs. Conducting mentoring in business people who have started to open a new business.